Wisata Swadaya Desa Berbasis Masyarakat dalam Meningkatkan Kelestarian Lingkungan dan Ekonomi Masyarakat Studi Kasus di Kelurahan Loloan Timur Kecamatan Jembrana, Bali - Fathurrahim (Jurnal Al-Tatwir, 2020)
In 2020 the Ministry of Environment and Forestry released the management report of 36,725,828.83 tons of waste. In Bali, especially at Kuta beach, the joint team cleaned up about 30 tons of garbage on January 1, 2021. Naturally, such condition is very concerning. However, it does not only occur on Kuta beach, but also on beaches and surrounding rivers located in Bali Province. Therefore, there is an emerging environmental movement of young people in East Loloan who call themselves DARLING or which stands for "Sadar Lingkungan" (environmentally aware). One of the things they did was building an ambenan on a riverbank which is now called Ambenan Ijogading. The current study employs a qualitative method. The data were collected by interviews, observation and documentation. The current study aims to: 1) find out the types and components of Ambenan Ijogading as a tourist attraction, 2) find out the form of community empowerment in Ambenan Ijogading, 3) find out the supporting and inhibiting factors for Ambenan Ijogading  as a tourist attraction. The results of this study are 1) Ambenan Ijogading tourist attraction is categorized as a naturally-occurring tourist attraction and also belongs to marine tourism. Meanwhile the tourism components include accommodations, food and culinary sector, attractions, and entertainment facilities. 2) The community empowerment found were done by maintaining the cleanliness of the surrounding environment as well as the cleanliness of the Ijogading river flow, painting the road to Ambenan Ijogading, and manufacturing natural liquid fertilizer. 3) The internal supporting factor is public awareness to develop tourist villages and the external factor is the many potentials that Loloan village possesses. The internal inhibiting factor is the limited human resources while the external inhibiting factor is the frequent flooding which results in frequent damaged facilities.